2020
DOI: 10.1039/c9nr06041c
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent down-shifting CsPbBr3 perovskite nanocrystals for flexible Cu(In,Ga)Se2 solar cells

Abstract: To overcome the parasitic absorption of ultraviolet (UV) light in the transparent conductive oxide (TCO) layer of flexible Cu(In,Ga)Se 2 (CIGS) thin film solar cells, a CsPbBr 3 perovskite nanocrystal based luminescent down-shifting (LDS) layer was integrated on CIGS solar cells fabricated on a stainless steel foil. The CsPbBr 3 perovskite nanocrystal absorbs solar irradiation at wavelengths shorter than 520 nm and emits photons at a wavelength of 532 nm. These down-shifted photons pass the TCO layer without p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…Compared with a relatively low PL QY (<50%) in Si QDs [31,32], IPQDs have PL QYs of 80%, 95%, 70%, for red, green, and blue emissions [33]. It has been reported that the spectral response with near UV light range of 300-390 nm of a Cu(In,Ga)Se 2 (CIGS) thin film solar cell was improved by taking advantage of the down-shifting effect of IPQDs [34]. In the present work, a colloidal approach is introduced to synthesize caesium lead bromide perovskite quantum dots (CsPbBr 3 QDs) that are cubic shaped with a mean size of 10 nm and whose room temperature PL peak is observed at 515 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with a relatively low PL QY (<50%) in Si QDs [31,32], IPQDs have PL QYs of 80%, 95%, 70%, for red, green, and blue emissions [33]. It has been reported that the spectral response with near UV light range of 300-390 nm of a Cu(In,Ga)Se 2 (CIGS) thin film solar cell was improved by taking advantage of the down-shifting effect of IPQDs [34]. In the present work, a colloidal approach is introduced to synthesize caesium lead bromide perovskite quantum dots (CsPbBr 3 QDs) that are cubic shaped with a mean size of 10 nm and whose room temperature PL peak is observed at 515 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Since the discovery of lead halide perovskite nanocrystals (NCs) in 2014, 1 these materials have been investigated as candidates for downconversion phosphors, 2 4 absorber layers in solar cells, 5 7 and emitting layers in light-emitting diodes (LEDs). 8 14 Important advantages of perovskite NCs are their facile synthesis 15 18 and their intrinsic defect tolerance.…”
mentioning
confidence: 99%
“…Furthermore, solar cells made of Cu 2 ZnSn(S,Se) 4 (CZTSSe) or Cu(In,Ga)(S,Se) 2 (CIGS) mainly use CdS as the buffer layer, which has the disadvantage of absorbing ultraviolet (UV) light [ 1 , 2 , 3 ]. To solve this narrow absorption band problem, researchers are studying luminescent down-shifting (LDS) layers that can widen the absorption bands via simpler methods than multijunction or tandem solar cells [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. The quantum dot (QD)-based LDS layer utilizes the properties of QDs that absorb light of short wavelengths and emit light with large wavelengths.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, more photons in the semiconductors lead to the generation of more electron-hole pairs, and the photovoltaic current increases. LDS layers have been applied to CdTe [ 7 ], silicon [ 9 , 10 , 11 ], and CIGS [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ] solar cells, but no results have been reported yet for CZTSSe solar cells. Lesyuk et al calculated the effects of QD-based LDS layers on Cu 2 ZnSnS 4 (CZTS) solar cells using the Monte Carlo ray-tracing method, but no experiments were described [ 5 ].…”
Section: Introductionmentioning
confidence: 99%